Identifying stakeholders’ needs for the use of electronic health records - Araújo, V.; Martins, A. L.; Correia, R. (Proceedings Euroma 2025, 2025)
Despite the growing implementation of Electronic Health Records (EHRs), there is limited understanding of patients' expectations and concerns regarding their use. This paper explores patients’ perspectives on using EHRs. Based on a systematic literature review, a questionnaire was developed to identify key perceived advantages (enhanced security, interoperability), barriers (technical challenges, privacy concerns), enablers (collaboration, user feedback), and requirements (interoperability standards, regulatory compliance) influencing the adoption of such wallets. With a sample of 63 respondents, findings highlight the need for accessible tools to accommodate less tech-literate users and contribute to designing truly patient-centric digital health solutions in healthcare operations management.